The Changes of Juveniles’ Cognitive Distortions, Social Skills and Problem Behavior Due to the Implementation of EQUIP Program at Lithuanian Children Socialization Centers - Klimukienė, Virginija; Kalpokienė, Vaida (Kriminologijos studijos, 2018)
[only abstract in English; full article and abstract in Lithuanian] There has been some great public concern regarding the provision of effective services for delinquent juveniles in order to decrease their untoward behavior and enable them to build further lives without any harm to either themselves or the others. The first results of the effectiveness research of cognitive-behavioral correctional program EQUIP, conducted in United States, where the program was first devised, have shown a great impact of the EQUIP program toward the decrease of delinquent behavior. However, the findings of further investigations in other countries remain controversial. The aim of this study was to measure the impact of the EQUIP program toward the changes of juveniles’ cognitive distortions, social skills and problem behavior at Lithuanian Children Socialization Centers. Quantitative research was conducted to compare the data of the EQUIP and comparison groups before and after the implementation of the EQUIP program. The study involved 124 juveniles (74 males and 50 females) aged 11-17 years. Assuming that the integrity of a correctional program might affect the results of the program’s impact, the following basic components of program integrity (Helmond et al., 2014) where secured while implementing the EQUIP program in Lithuania: 1) Exposure; 2) Adherence; 3) Participant responsiveness; 4) Quality of implementation. The results of the study revealed significant differences of thinking errors, social skills and problem behavior before and after the participation in the EQUIP program, while differences in the abovementioned variables within the comparison group were either absent or insignificant. Based on the results of the study, the intensity of the EQUIP program implementation (5 times per week vs. 4 or less times per week) is an important provision for the increase of the effectiveness of the EQUIP program. Moreover, the age of participants (above 14 years old) is a very important factor to safeguard the changes in cognitive and behavioral variables. It is recommended that further studies on the impact of the EQUIP program are focused on the evaluation of changes of criminal recidivism rates in a long-term perspective as well as criminal attitudes. Moreover, the participation in the EQUIP program should be related to the level of criminal risk, whenever the measure of it is available in Lithuania.